Silhouetting the Shifting Perspective of Bollywood from ‘Machismo’ to ‘Metrosexuality’ - Bhattacharjee, Partha; Tripathi, Priyanka (Journal of English Language and Literature (ISSN: 2368-2132), 2017)
“Machismo” and “Metrosexual” are two trending but contradictory terms that are used to fathom the portrayal of men in the visual art such as cinema, media, advertisements etc. Derived from the Spanish word ‘Macho’, ‘Machismo’ reflects strength, aggression and masculine pride whereas ‘Metrosexual’ is a portmanteau word combining– ‘Metropolitan’ and ‘Sexual ‘referring to men who are living in an urban society and investing a great deal on their appearance and lifestyle. The paper intends to focus on the transition of this portrayal of men in Hindi films, popularly termed as Bollywood. To elucidate further the paper will take its references from the films of the Sholay era till the contemporary times in which films like Ki n Ka changed the sketch, the set and the setting of the male word/world. In between these two films, one can truly demarcate the world of Hindi films in terms of how the audience will see their men. Therefore, the paper, broadly taking its references from Hindi Films, Advertisements and Daily Soaps will establish the men’s makeover over a period of time.